Effects of physical habitat degradation on the stream fish assemblage structure in a pasture region - Casatti, Lilian; Langeani, Francisco; Ferreira, Cristiane P. (Springer, 2006)
We compared the fish assemblage structure from streams with different intensities of physical habitat degradation and chemical water pollution by domestic sewage in southeastern Brazil. Eight streams (R1-R8) showing less disturbed or more disturbed conditions of chemical water quality and of physical habitat quality were selected. Cumulative abundance and biomass, combined in ABC plots, revealed (i) biomass curves above the abundance curves, represented by the streams R1-R2 (water and habitat less disturbed) and R5-R6 (water more disturbed and habitat less disturbed), and (ii) biomass curves below the abundance curves, represented by the streams R3-R4 (water less disturbed and habitat more disturbed) and R7-R8 (water and habitat more disturbed). The quantitative structure of the ichthyofauna showed significant correspondence with physical habitat condition but not with chemical water quality. The most significant species to cause the dissimilarity between less disturbed and more disturbed physical habitats was the exotic Poecilia reticulata. Such results indicate that in the focused region-with little influence of industrial pollution, noncritical domestic sewage discharge, and soil predominantly used for pasture-streams with high physical habitat integrity possess a differently structured ichthyofauna than streams with relatively low physical habitat integrity, reinforcing the importance of the physical habitat quality and riparian conservation along these water courses, warranting the conservation of these systems. Indeed, our results also reinforce the importance of including biotic descriptors, particularly of the ichthyo-fauna, in water-monitoring programs designed to reveal signs of human interference.
Keywords: ABC plots; monitoring; diversity; stream fishes; upper Rio Parana